Penerapan Prinsip-Prinsip Good Governance Pemerintah Desa Ujungnge Kecamatan Tanasitolo Kabupaten Wajo - Patmasari, Eka; Ilham, Ilham (JURNAL EKOLOGI BIROKRASI, 2022)
This paper aims to determine the application of the principles of good governance in Ujungnge Village Government, Tanasitolo District, Wajo Regency. This study was conducted using a qualitative descriptive research method. Data was obtained through observation, interviews, documentation, and literature study. Furthermore, data analysis was carried out through several stages; data reduction, data presentation, and conclusion drawing. The results of this study indicate that the application of the principles of good governance in the Ujungnge Village Government, Tanasitolo District, Wajo Regency, is seen from participation, transparency, and accountability. Community participation in every activity carried out by the village government is still considered lacking, the transparency of the village government so far in carrying out its duties has improved, and the implementation of the principle of accountability by the village government has also been going well. It can be seen that every village development program has been running according to its stages starting from; planning, development, monitoring, and reaching the accountability stage. In an effort to achieve good governance, the Ujungnge Village Government is faced with several problems, such as; a lack of community participation and lack of support from Human Resources (HR), especially regarding the mastery of technology by the village apparatus. As a recommendation, the knowledge of village officials should be further improved, including in relation to the use of technology through training and education so that the performance of village officials will improve.